Annealing effects on optical properties of natural alexandrite - Scalvi, RMF; Li, M. S.; Scalvi, LVA (Iop Publishing Ltd, 2003)
Natural alexandrite (BeAl2O4:Cr3+) crystals are investigated as regards the effects of annealing on their optical properties. Optical absorption spectra are measured from the ultraviolet (190 nm) to the near infrared (900 nm), for a sample subjected to consecutive annealing processes, where time and temperature are varied. Besides this, luminescence spectra are simultaneously obtained for this sample, excited with a Kr+ laser source, tuned on an ultraviolet multi-line mode (337.5, 350.7 and 356.4 nm). We observe from absorption as well as from emission data that annealing mainly influences the distribution of Cr3+ and Fe3+ ions, located on sites of a mirror plane (C-s symmetry), which are responsible for the optical properties of alexandrite. The results obtained lead to the conclusion that annealing induces a modification of the population of Cr3+ on C-s sites as well as on sites located on an inversion plane (C-i). Annealing could improve the optical properties of this material, as regards its application as a tunable laser.